Evaluating the Interaction Between Chelated Iron Source and Placement on Phosphorus Availability in Soybean - C. L. Edwards; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2016)
In agriculture, chelating agents are used to supplement micronutrients, such as iron (Fe). However, little research has been conducted at the field-scale level to evaluate chelating agent effects on phosphorus (P). The objectives of this study were to evaluate three commercially available chelated Fe sources on early soybean growth and nutrient uptake. The study was conducted at six locations in 2014 and 2015. The experimental design was a randomized, complete block with a factorial treatment arrangement. The two factors included fertilizer source and fertilizer placement. The fertilizer sources were P only, EDTA-Fe, HEDTA-Fe, and one glucoheptonate product, Cee*Quest N5Fe758 (CQ-758), with two fertilizer placements, in-furrow with seed contact and surface band at planting. Results show soybean yield was affected by chelate source and placement. Greater yields occurred with application in-furrow at Scandia in 2014 and 2015, but in-furrow was superior at Rossville in 2015. Increased yields also occurred with applications of EDTA and HEDTA. However, further analysis of tissue and grain may show chelate effects on nutrients.
Keywords: phosphorus; soybean; chelating agents; fertilizer; placement